Representasi Bromance dalam Novel Dikta dan Hukum Karya Dhia’an Farah (Analisis Semiotika Roland Barthes) - Nadofah Nadofah; Firman Hadiansyah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
Some people have a bad view of friendship between men. Even though many of them have closeness just to share stories and problems that cannot be told to their partners. The purpose of this study is to describe the forms of bromance representation contained in the novel Dikta dan Hukum by Dhia'an Farah using Roland Barthes' semiotic theory. This is done to analyze the meaning of a quote that represents a picture of closeness among men and then relates it to phenomena in society. The research method used is descriptive qualitative method. Data collection was carried out using documentation techniques, data analysis techniques in the form of work analysis. The results of the study show that the forms of bromance include: mutual affection, emotional support, protection, and pleasure in each other's presence.